A Polity on the Edge : Canada and the Politics of Fragmentation - Clarke, Harold D. (Book collections on Project MUSE., 2000)
"This is a book about forces challenging the continued integrity of Canada, one of the world's oldest and most admired democracies. It focuses on six critical events, beginning with the 1988 federal election and the fierce debate over the risks of free trade with the United States for Canada's economy and cherished social programs. It ends with the 1998 re-election of the Parti Quebecois and the possibility of a third sovereignty referendum. Collectively, these events have pushed Canada to the edge of disintegration. The book's analyses and interpretations of these events are based on a collection of survey data gathered over the past two decades. Conversations with thousands of Canadians map the dynamics of public beliefs, attitudes and behaviour in an era of economic dislocation and political crisis. Struggling to adapt its political institutions and processes to regional and ethno-linguistic cleavages invigorated by forces of economic restructuring and globalization, Canada exemplifies many of the "forces from above and below" that have beset democracies, new and old alike, in recent years. By explaining how these forces have brought a "charter member" of that very special political club to the brink of fragmentation, this book will be of interest to all those concerned with the future of democracy in polycommunal societies."--Jacket